2013
DOI: 10.15376/biores.8.4.6121-6135
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance-Tensile-Strength Alpha-Grass Reinforced Starch-Based Fully Biodegradable Composites

Abstract: aThough there has been a great deal of work concerning the development of natural fibers in reinforced starch-based composites, there is still more to be done. In general, cellulose fibers have lower strength than glass fibers; however, their specific strength is not far from that of fiberglass. In this work, alpha-fibers were obtained from alpha-grass through a mild cooking process. The fibers were used to reinforce a starch-based biopolymer. Composites including 5 to 35% (w/w) alpha-grass fibers in their for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
1
10
1
Order By: Relevance
“…The 150-min treatment was chosen as satisfactory for obtaining AF with enough stiffening capabilities. Moreover, in a recent article (Gironès et al 2013) the authors found that the same cooking time was enough to obtain fibers with the required quality to create good fiber-matrix interphases. If the data are introduced in the rule of mixtures (Eq.…”
Section: Chemical Characterization Of the Alpha-grass Stalksmentioning
confidence: 99%
See 3 more Smart Citations
“…The 150-min treatment was chosen as satisfactory for obtaining AF with enough stiffening capabilities. Moreover, in a recent article (Gironès et al 2013) the authors found that the same cooking time was enough to obtain fibers with the required quality to create good fiber-matrix interphases. If the data are introduced in the rule of mixtures (Eq.…”
Section: Chemical Characterization Of the Alpha-grass Stalksmentioning
confidence: 99%
“…The main goal of cooking the alpha-grass was to remove the extractives and ash, thus obtaining neat fibers with high cellulose content and a surface capable of chemical interaction. A good fiber-matrix interphase is very important for obtaining composite materials with good mechanical properties (tensile, flexural, and impact strength) (Girones et al 2013). Moreover, it is important to retain the lignin content, as it influences the intrinsic modulus of the fibers, and at the same time has little influence in the fiber-matrix interaction (Neagu et al 2006).…”
Section: Chemical Characterization Of the Alpha-grass Stalksmentioning
confidence: 99%
See 2 more Smart Citations
“…Starch is the second most abundant renewable polymer found in nature after the lignocellulose group and it is relatively inexpensive (Girones et al 2013). Because of its low cost, renewability, biodegradability, and lack of toxicity or smell, it has been considered for many years to have high potential for use in packing and disposable items instead of petroleum-based polymers (Kaewtatip and Thongmee 2013;Zuo et al 2014).…”
Section: Introductionmentioning
confidence: 99%